The effect of topical administration of sildenafil in acute ocular hypertension model in rabbits. - Matloub, Samir Y. N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Nitric oxide ( NO) is a physiological mediator of many processes in the eye including regulation of aqueous humor dynamics. Compounds acting via NO dependent mechanisms may enhance aqueous humor outflow and reduce intraocular pressure (IOP) .Objective: Sildenafil a cGMP specific phosphodiesterase 5inhibitor that potentiates NO production and increases cyclic GMP is tested in this study for its effects on intraocular pressure in an acute ocular hypertension model in rabbits.Materials and methods: Newzealand albino rabbits of either sex weighing 2–2.5 Kg , were used in this study. Sildenafil was prepared in a vehicle of phosphate buffer and diluted to the required strength of 0.5%. Intraocular pressure (IOP ) was measured after 45 seconds of one drop of proparacaine topical anesthesia by using schiotz indentation tonometer. Basal IOP was obtained for both eyes using 12 rabbits .One drop of sildenafil (0.5%) was then topically instilled in the left eye while the right eye received the vehicle and served as a control. After 30 minutes of drug and vehicle administration the IOP was measured in both eyes and acute ocular hypertension was induced by the administration of 15ml/kg 5% glucose. The IOP was then recorded every 15 min for 180 minutes.Results: Topical 0.5% sildenafil administration had no effect on the basal IOP levels. However sildenafil significantly (p < 0.05) attenuated the acute rise in IOP induced by 5% glucose infusion. The IOP levels returned to their basal values in shorter time with sildenafil compared to the controlConclusion: Topical sildenafil pretreatment reduces IOP in acutely induced intraocular hypertension.